Atores políticos do pentecostalismo católico e evangélico paulista - Manduca, Vinicius (2015)
This work stems from research earlier work of scientific initiation with FAPESP grant, also supervised by Prof. Dr. André Ricardo de Souza. There was a deepening of political reality research that had as starting point the elections to the Constituent Assembly of 1986. These set a new stage for Brazilian politics, marked by the inclusion of groups linked to Pentecostal churches. For the election, a system based on the figure of the "official candidate" was established that in addition to considerably increase the number of evangelicals in the legislative houses, also modified forms of political action that environment, generating an Evangelical Parliamentary Front, for example. On the other hand Catholicism, who faces constant demographic decline, is also manifesting itself more directly in the political arena, differently from that of Liberation Theology. Known as the "Catholic Pentecostalism," the Charismatic Renewal gradually brings also to the political field itself, elements of Pentecostal evangelical action. This paper presents a comparative analysis of such Christian spectrum, focusing on one representative for each one, as to their political activities, involving the differences and similarities of the forms of electoral and parliamentary action.